REVEALING THE GENDER INEQUALITY IN PATRICIA MC. CORMICK’S SOLD CRITICAL DISCOURSE ANALYSIS - Ririn Fatmawati; Sukarno Sukarno; Ikwan Setiawan (Universitas Sebelas Maret, 2017)
This study aims to reveal the gender inequality between male and female in the novel entitled Sold. It is the representation of Nepalese culture in social life. The data sources data are the novel of Sold. The data in this study are in the form of words, phrases, and sentences that found in the Sold which contains gender inequality. Critical discourse analysis by Van Dijk’s theory is applied in this study. The result of this study shows that male tends to dominate over female. Male points how irresponsibility they are to their own family. Moreover, women have limited decision powers. They will be abandoned by their husbands and they are not allowed to make their own choices due to cultural or religious instructions.Keywords: Gender inequality, critical discourse analysis, sold, domination.